Physico-chemical properties of optimized Kaalan-A traditional dairy product: Optimization of Kaalan - K B, Divya; P, Sujith; S. N., Rajakumar; A.K., Beena; M.P., Divya; P., Sudheer Babu; V., Ramnath (Indian Journal of Dairy Science, 2024)
Kaalan is a buttermilk, coconut, and vegetable-based culinary preparation filled with the goodness of spices, famous in the South Indian state of Kerala. The Kaalan available in the market differs widely which can be attributed to a lack of well-defined characterization and standardization, hindering efforts towards industrial production. The complex procedures of preparation and lack of knowledge limit its preparation to caterers and households. The current study aimed to optimize the production process utilizing the Response Surface Methodology for achieving standardized large-scale production within the organized sector. The outcomes from the Response Surface Methodology (RSM) demonstrated that the experimental observations could be suitably accommodated within a second-order polynomial model, exhibiting a satisfactory coefficient of determination (R2 > 90%). The proposed formulation for the Kaalan was a combination containing 194.97g vegetable, 748.09 ml buttermilk, and 126.78g coconut. The optimized Kaalan had 3.49±0.005 per cent protein, 7.12±0.07 per cent fat, 9.95±0.08 per cent carbohydrate, 4.84±0.22 per cent dietary fiber, 2.17±0.03 per cent ash and 28.36±0.04 per cent total solids. The curcumin content was 13.63±0.03 per cent and the energy value was 117.77±0.42 kcalories per 100 g. The data shows that the optimized Kaalan can be established as a nutritionally valuable, low-calorie functional food.